Implementing shared decision making in the NHS. (14th October 2010) - Elwyn, Glyn; Laitner, Steve; Coulter, Angela; Walker, Emma; Watson, Paul; Thomson, Richard
Abstract : Creation of a platform of tools to provide information to doctors and patients should be the first step in giving patients choice about their treatment, say Glyn Elwyn and colleagues .